1998
DOI: 10.1097/00006123-199811000-00061
|View full text |Cite
|
Sign up to set email alerts
|

Posterior Fossa Reexploration for Persistent or Recurrent Trigeminal Neuralgia or Hemifacial Spasm: Surgical Findings and Therapeutic Implications

Abstract: Recurrent vascular compression was seldom identified during posterior fossa reexploration for failed MVD in patients with persistent or recurrent TN or HFS. The previously placed Ivalon sponge or Teflon implant was consistently found to be in good position. Partial sensory trigeminal rhizotomy is an often effective alternative in cases of recurrent TN when neurovascular compression is not identified. However, because of the relatively high incidence of complications associated with reexploration, we recommend … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
93
0
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(97 citation statements)
references
References 19 publications
2
93
0
2
Order By: Relevance
“…At repeat surgery, the vessel may sometimes be better mobilized, although not at the expense of any perforators. As in prior reports, success rates have generally been lower than reported for initial surgery, 3,16,25 although we found that two-thirds of patients became spasm-free after our own repeat MVD. Similar to the results of our study, Barker and Jannetta did differentiate the results of surgery between patients treated initially by their own group versus other centers and found repeat MVD cure rates to be significantly higher in the latter.…”
Section: Repeat Mvd Techniquesupporting
confidence: 53%
“…At repeat surgery, the vessel may sometimes be better mobilized, although not at the expense of any perforators. As in prior reports, success rates have generally been lower than reported for initial surgery, 3,16,25 although we found that two-thirds of patients became spasm-free after our own repeat MVD. Similar to the results of our study, Barker and Jannetta did differentiate the results of surgery between patients treated initially by their own group versus other centers and found repeat MVD cure rates to be significantly higher in the latter.…”
Section: Repeat Mvd Techniquesupporting
confidence: 53%
“…[8] Although some papers showed limited improvement with a high complication rate for preoperative MVD, [1,10] recent surgical results of late reoperation didn't show significant differences from those undergoing their initial MVDs. [16,21] Our results showed that cumulative spasm free rate at 3 months after operation was 97%.…”
Section: Assessment Of Persistent Spasm After Mvdmentioning
confidence: 99%
“…Patients who underwent a repeat MVD procedure for either trigeminal neuralgia or hemifacial spasm were excluded as reoperations may pose higher risks to cranial nerves than a first MVD. 17 During the study period, 3 patients were referred for treatment because of recurrent symptoms and underwent repeat MVD; they were excluded from this study. The patient population was divided into two groups.…”
Section: Patient Populationmentioning
confidence: 99%